ACCUMULATION OF MAGNETIC POLLUTION AND HEAVY METALS IN SOILS AND VEGETATION OF KYIV CITY - BONDAR, K.; SAMCHUK, A.; STAKHIV, I.; SLOBODIANYK, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Magnetic susceptibility of soils, tree bark and leaves from Kyiv megalopolis was measured. Significant correlation between soil magnetic susceptibility and contents of Ni, Pb, Cu and Zn was found. The tendency for increase of magnetic susceptibility of leaves due to airborne pollution was observed.